2013
DOI: 10.1097/bot.0b013e31828e1bb7
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative Treatment of the Medial Malleolus in Bimalleolar and Trimalleolar Ankle Fractures

Abstract: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 23 publications
0
44
2
Order By: Relevance
“…However long-term follow-up is needed due to increased risk of nonunion and uncertainity regarding the development of posttraumatic arthritis. 22 Hong et al in 2014 evaluated the clinical and functional outcome of trimalleolar fractures and the ability of patients to return to sporting activities. In their retrospective study of 31 patients they found that 11 patients had residual pain, 13 patients had persistent ankle stiffness, 10 patients had swelling at 1 year follow up.…”
Section: Inferencementioning
confidence: 99%
“…However long-term follow-up is needed due to increased risk of nonunion and uncertainity regarding the development of posttraumatic arthritis. 22 Hong et al in 2014 evaluated the clinical and functional outcome of trimalleolar fractures and the ability of patients to return to sporting activities. In their retrospective study of 31 patients they found that 11 patients had residual pain, 13 patients had persistent ankle stiffness, 10 patients had swelling at 1 year follow up.…”
Section: Inferencementioning
confidence: 99%
“…Contemporary nonoperative management is generally recommended for isolated fractures that are nondisplaced or minimally displaced (≤2 mm), for avulsion injuries, for staging surgery as a result of compromised soft tissues, and for cases where medical comorbidities or patient preferences exclude operative in-tervention. 41 However, the literature has not consistently shown the superiority of operative management over nonoperative management. However, for nonunion or malunion, the decreased contact area and increased contact pressures have been found to be significant.…”
Section: Indications For Nonoperative Managementmentioning
confidence: 99%
“…Operative management is favored, 37,[45][46][47][48][49][50] but some studies found no difference in clinical or radiographic outcomes. 41,51 Tornetta 6 retrospectively reviewed a series of 27 bimalleolar ankle fractures and found that the size of the medial malleolar fragment was the most significant predictor of deltoid competence. This study found that the deltoid ligament was incompetent and the ankle was unstable on external rotation stress radiographs after fixation of all medial malleolar fractures less than 1.7 cm wide on lateral radiograph.…”
Section: Bi-and Trimalleolar Ankle Fracturesmentioning
confidence: 99%
“…However, long-term follow-up is needed due to increased risk of non-union and uncertainty regarding the development of posttraumatic arthritis. 22 Hong et al in 2014 evaluated the clinical and functional outcome of trimalleolar fractures and the ability of patients to return to sporting activities.…”
Section: Slmentioning
confidence: 99%